THEORETICAL BASES OF FUNCTIONING OF A COMPLEX HYDRODRIVE OF COMBINE HARVESTERS - Vladimir N. Geleverov; Anatoly D. Dyachenko (Advanced Engineering Research, 2010)
The generalised basic scheme of a complex hydraulic drive of self-propelled combine harvesters and theoretical bases of functioning of these drives is presented.